Supply chain management in pharmaceutical industries: a study on Eskayef Bangladesh Ltd. - Moniruzzaman, Dr. Md. (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.